2020
DOI: 10.1186/s12890-020-1119-9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic profiling aids in understanding the lesion origins of a patient with six synchronous invasive lung adenocarcinomas: a case study

Abstract: Background: Synchronous multiple primary lung cancers (sMPLC) are rare forms of lung cancer, and their diagnosis remains as a significant challenge. Distinguishing sMPLC from advanced disease is important as their prognoses and therapeutic management vary dramatically. Case presentation: The patient was a 56-year-old Chinese male who exhibited six synchronous invasive adenocarcinomas at diagnosis [T2(6)N0M0], and who achieved durable clinical benefit under adjuvant chemotherapy for 41 months following wedge re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Apart from histopathological reports used as a golden standard, genetic analyses of the clonal origin of tumors are useful because these can help to determine whether MPLC have arisen from the same clone and therefore the same tumor [1,16]. Song et al [17] reported a patient with six synchronous invasive adenocarcinomas that were revealed due to whole-exome sequencing and analysis of nonsynonymous mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from histopathological reports used as a golden standard, genetic analyses of the clonal origin of tumors are useful because these can help to determine whether MPLC have arisen from the same clone and therefore the same tumor [1,16]. Song et al [17] reported a patient with six synchronous invasive adenocarcinomas that were revealed due to whole-exome sequencing and analysis of nonsynonymous mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The development of MPLCs is an interesting phenomenon because it arises from an identical germline genetic background and environmental exposure and yet results in highly heterogeneous lesions. Previous studies on the molecular and genomic data of MPLCs have found that tumours developing in this context show clonally distinct molecular profiles, distinct oncogenic alterations, and can be of a different pathological type [ 18 , 19 , 20 , 21 ], suggesting variable responses of MPLCs to targeted therapies, and strong implications for the therapeutic management of MPLC patients. We describe a rare case of MPLCs, harbouring a mixed histology of SCLC and NSCLCa, which we analyse through whole genome sequencing.…”
Section: Introductionmentioning
confidence: 99%